2022
DOI: 10.1007/s40333-022-0071-3
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and analysis of snow cover change in an alpine mountainous area in the Tianshan Mountains, China

Abstract: Estimating the snow cover change in alpine mountainous areas (in which meteorological stations are typically lacking) is crucial for managing local water resources and constitutes the first step in evaluating the contribution of snowmelt to runoff and the water cycle. In this paper, taking the Jingou River Basin on the northern slope of the Tianshan Mountains, China as an example, we combined a new moderate-resolution imaging spectroradiometer (MODIS) snow cover extent product over China spanning from 2000 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…5 ). The evolution of snow cover is the most active in Low relief middle altitude mountain, and the evolution of snow cover is the most stable in Middle relief high altitude mountain, The same as the altitude distribution of SCP in the high altitude area of Tianshan region reported by Zhang 45 . There is also a strong correlation between the variation of snow cover and the slope gradient.…”
Section: Discussionsupporting
confidence: 61%
“…5 ). The evolution of snow cover is the most active in Low relief middle altitude mountain, and the evolution of snow cover is the most stable in Middle relief high altitude mountain, The same as the altitude distribution of SCP in the high altitude area of Tianshan region reported by Zhang 45 . There is also a strong correlation between the variation of snow cover and the slope gradient.…”
Section: Discussionsupporting
confidence: 61%
“…Since the 1960s, precipitation in the Tianshan Mountains has been continuously increasing, and the increase has become more significant since the 1980s. The increase in summer precipitation is the largest, and mountainous precipitation shows a clear increasing trend Zhang, Liu, and Tang 2013). Based on the spatiotemporal distribution characteristics of different precipitation intensities in the Qilian Mountains and their relationship with altitude, previous studies have concluded that, apart from the influence of altitude, the height zone of maximum precipitation in the Qilian Mountains is likely to be closely related to the occurrence of maximum relative humidity centers at high and low altitudes and the corresponding centers of strong cold air activity .…”
Section: Introductionmentioning
confidence: 99%
“…For snowmelt forecasting, it is important to understand first the relationship between the meteorological influencing factors and snowmelt runoff before identifying the critical influencing ones (Vasil Ev et al, 2013). Common methods used in previous studies include, for instance, by analyzing the correlation coefficient between each factor and snowmelt runoff (Nabi et al, 2011;Zhang et al, 2014), or applying a local sensitivity analysis of individual factors (Zhang et al, 2016;Stigter et al, 2017;Zhang et al, 2022). However, these methods often failed to consider the joint effects of multiple factors.…”
Section: Introductionmentioning
confidence: 99%